Analisis SWOT untuk Menyusun Pengembangan Strategi Promosi Digital UMKM Hataraya Food di Kota Malang - Nur Afni Mauludia; Eko Boedhi Santoso; Ayu Sulasari (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the internal and external conditions of Hataraya Food, a snack MSME in Malang City, and formulates appropriate digital promotion strategies using SWOT analysis. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation involving the business owner, employees, and consumers. The analysis utilized the IFE Matrix, EFE Matrix, SWOT Quadrant, and SWOT Matrix. The findings reveal that Hataraya Food's digital promotion through Instagram has not been optimally managed, resulting in low consumer engagement and limited market reach. Based on the IFE and EFE Matrix analysis, Hataraya Food is positioned in Quadrant I (Growth Oriented Strategy) with coordinates (3.1 : 2.68), indicating that the business possesses internal strengths that can be leveraged to seize external opportunities. The recommended strategy is the SO (Strengths-Opportunities) Strategy, which involves utilizing the quality of homemade products and distinctive taste as the main focus of digital promotional content, increasing promotional intensity through various Instagram features (feed, story, reels, highlight), developing creative content variations, expanding marketing through marketplaces such as Shopee, Tokopedia, and TikTok Shop, and maintaining consistent uploads through a planned content schedule. The study also recommends regular evaluation of digital marketing performance based on reach, engagement, and consumer responses to continuously adapt the strategy to evolving market needs and digital media trends.